STRESS AND COPING AMONG NEWLY HIRED EMPLOYEES IN PRIVATE SECTOR IN MALAYSIA - Muhammad Rizki (STIE PEMBANGUNAN TANJUNGPINANG, 2018)
Stress is unavoidable in human life, including in working environment. Many researchers have reported different source of the stress and coping methods for the employees in general. However, little has been done to explore the source of the stress and coping methods specifically for newly hired employees. This study, using qualitative design, tried to look at the source of the stress in working environment specifically for the newly hired employees. Data were collected through interview with 4 participants who are working in private sector in Malaysia. The result of the study shows that the source of stress ranging from the nature of the job, task related stressor, new environment and also unsupportive environment, and their coping methods including escapism, seek for social support and informational help. This result, however cannot be generalized, however, it may help in understanding and appreciate the uniqueness in employees perception of stressors and effective coping methods